Multiethnic Social Interaction and Cultural Acculturation among Kapuas Riverbank Communities in Pontianak City - Tata Ihsan; Patriaman Tanjung; Embun Afifah Honey; Mega Amanda; Dewi Cindia Putri; Kofoworola Gboyega (CV. Yazri Aksara Nusantara, 2026)
This study is motivated by the development of multiethnic social interaction and cultural acculturation among communities living along the Kapuas River in Pontianak City as part of multicultural urban society. The study aims to analyse interethnic social interaction patterns and cultural acculturation processes formed through the social amultietnisof riverbank communities. This research employed a qualitative approach with a descriptive design. Data were collected through participant observation, in-depth interviews, and documentation involving communities in Kampung Wisata Benua Melayu Laut. The findings reveal that social harmony develops through intercultural communication, shared social spaces, river-based economic activities, and collective participation in cultural activities. Cultural acculturation is reflected in the use of Pontianak Malay as a shared communication language, cross-ethnic involvement in socio-cultural activities, and the presence of local cultural symbols representing multicultural cultural integration. The study also found that modernisation and digital technological development have influenced the sustainability of local riverbank culture. These findings highlight the importance of inclusive social spaces and cultural communication in strengthening social cohesion within multicultural urban communities.Penelitian ini dilatarbelakangi oleh berkembangnya interaksi sosial multietnis dan proses akulturasi budaya pada masyarakat bantaran Sungai Kapuas di Kota Pontianak sebagai bagian dari kehidupan masyarakat multikultural perkotaan. Penelitian bertujuan menganalisis pola interaksi sosial antaretnis serta proses akulturasi budaya yang terbentuk melalui aktivitas sosial masyarakat tepian sungai. Penelitian menggunakan pendekatan kualitatif dengan desain deskriptif. Data diperoleh melalui observasi partisipatif, wawancara mendalam, dan dokumentasi terhadap masyarakat di Kampung Wisata Benua Melayu Laut. Hasil penelitian menunjukkan bahwa harmonisasi sosial masyarakat berkembang melalui komunikasi antarbudaya, penggunaan ruang sosial bersama, aktivitas ekonomi sungai, dan partisipasi kolektif dalam kegiatan budaya masyarakat. Proses akulturasi budaya terlihat melalui penggunaan Bahasa Melayu Pontianak sebagai bahasa komunikasi bersama, keterlibatan lintas etnis dalam aktivitas sosial budaya, serta keberadaan simbol budaya lokal yang merepresentasikan integrasi budaya masyarakat multikultural. Penelitian ini juga menemukan bahwa modernisasi dan perkembangan teknologi digital mulai memengaruhi keberlanjutan budaya lokal masyarakat tepian sungai. Temuan penelitian menegaskan pentingnya ruang sosial inklusif dan komunikasi budaya dalam memperkuat kohesi sosial masyarakat multietnis perkotaan.